Agroecological living landscapes toolkit - Voss, Rachel C.; Freed, Sarah; Fuchs, Lisa Elena; Triomphe, Bernard; Bergamini, Nadia; Dickens, Chris; Quintero, Marcela (2024)
This toolkit presents a structured approach—centered around developing Agroecological Living Landscapes (ALLs)—through which external partners can respectfully and productively foster knowledge co-creation and innovation co-design to accompany and support local stakeholders on their agroecological transformation pathways. While developed initially to support external actors’ engagement with local communities and stakeholders, the ALL approach is also relevant to community-driven transformation processes. It purposefully brings together diverse stakeholders, with a focus on connecting farmers with other food system actors in pursuit of a shared vision.